Preeclampsia is associated with low placental transthyretin levels - Lei Zhu; Dora Baczyk; Stephen J. Lye; Zhenyu Zhang (Taiwanese Journal of Obstetrics & Gynecology, 2016)
Objective: To investigate the relationship between placental transthyretin (TTR) level and preeclampsia. Materials and Methods: Placental tissues from uncomplicated and preeclamptic pregnancies were analyzed using immunohistochemistry and image analysis. We measured the mean optical density (OD) of immunohistochemical staining of TTR across multiple sections using Image Pro Plus 6.0. To avoid bias, we used placental tissue array, which contained preeclamptic placentas (n = 8) and the control placentas (n = 6) on the same slide. Results: The mean TTR OD of the syncytiotrophoblast layer of placentas (95% confidence interval) from the first trimester was higher than those from the second/third trimester, and term placentas [0.149 (0.014–0.285) for the 1st trimester, 0.037 (0.000–0.073) for the 2nd/3rd trimester, and 0.011 (0.035–0.056) for term; p < 0.01]. Although the OD of the second/third trimester placentas appeared greater than that of term placentas, this was not statistically significant. The mean TTR OD of the syncytiotrophoblast layer of the severe preeclampsia group was lower than that of controls [0.010 (0.005–0.016) vs. 0.027 (0.013–0.041), p < 0.05]. Conclusion: The immunohistochemical expression of TTR in the syncytiotrophoblast layer of the placenta decreased significantly after 12 weeks of gestation, paralleling the changing demands of thyroid hormone uptake into the placenta. The reduced TTR expression in the syncytiotrophoblast layer of the preeclamptic placenta might impair thyroid hormone uptake and contribute to the pathophysiology of the disease.